Dynamics of Job Quitting among High Educated Female Former Employees - Utama, J. Seno Aditya (International Research Journal of Business Studies, 2012)
The number of highly educated woman workers increased in recent year, but job quitting and woman career discontinuity was still high; it was related to working inequalities and work-family issues. The current study investigates the antecedent of woman job quitting decision, career aspiration, spouse and supervisor support. Individual in-depth interviews investigated the 12 highly educated ex-employee mothers. The findings were spouse support on woman job quitting, children care orientation, supervisor retention effort, current positive evaluation and unintended future career